2020
DOI: 10.1080/00313831.2020.1833241
|View full text |Cite
|
Sign up to set email alerts
|

Special Education Teachers’ Identification of Students’ Reading Difficulties in Grade 6

Abstract: This study investigated special educational needs (SEN) teachers' (n = 29) assessment practices and the accuracy of their ratings of the students' (M age = 12.75 years, n = 55) skill levels in reading fluency and reading comprehension. Teachers rated their sixth grade students' fluency and comprehension on a three-point scale, and the students were also tested in group tests. Results showed that SEN teachers used several assessment practices simultaneously but mostly relied on observations. The correlations be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 59 publications
0
4
0
1
Order By: Relevance
“…Third, we did not address the methods used by SEN teachers to identify support needs or to provide support, although teachers' ability and their approach to identifying reading difficulties in Grades 1 and 6 have been explored in recent studies using the same follow-up data (Virinkoski et al, 2018;Virinkoski et al, 2020). To deepen understanding of the relationship between part-time special education and skills development, it would be useful to incorporate earlier evidence.…”
Section: Limitationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Third, we did not address the methods used by SEN teachers to identify support needs or to provide support, although teachers' ability and their approach to identifying reading difficulties in Grades 1 and 6 have been explored in recent studies using the same follow-up data (Virinkoski et al, 2018;Virinkoski et al, 2020). To deepen understanding of the relationship between part-time special education and skills development, it would be useful to incorporate earlier evidence.…”
Section: Limitationsmentioning
confidence: 99%
“…Unfortunately, it seems clear that this support does not help these students to catch up with their peers in terms of academic skills. Although the Finnish education system allocates significant resources to early needs-based support of this kind, support decisions generally depend on teachers' observations (Virinkoski et al, 2018;Virinkoski et al, 2020), and it appears that SEN teachers may lack both the time and the competence to help students with multiple learning challenges (see Cancio et al, 2018;Langher et al, 2017). It seems likely that more effective and individually targeted methods of assessment and support are needed for these students, but further research is needed to clarify this issue.…”
Section: Conclusion and Implications For Practicementioning
confidence: 99%
“…children who may experience spelling difficulties in school (Kolne, Gonnerman, Marquis, Royle, & Rvachew, 2016), but no relevant research was found in the context of assessing students' spelling skills at school. The accuracy of support specialists' judgements has been particularly understudied, with few relevant studies being conducted in Finland (Virinkoski, Lerkkanen, Holopainen, Eklund & Aro, 2017;Virinkoski, Lerkkanen, Eklund & Aro, 2020). One of these studies found that special educators' judgements were more accurate than those of classroom teachers, but identifying children with weak phonological skills were still challenging (Virinkoski et al, 2017).…”
Section: Practitioner Pointsmentioning
confidence: 99%
“…Hasil evaluasi menunjukkan bahwa kegiatan pelatihan ini meningkatkan pemahaman guru dan orang tua terhadap paradigma pendidikan inklusi, serta meningkatkan kemampuan gurudan orang tua dalam pelaksanaan identifikasi ABK karena penggunaan mobile application berbasis android ini sangat membantu dan memudahkan dalam mengidentifikasi ABK dengan berbagai ketunaan, karena aplikasi identifikasi ABK ini mengakomodir identifikasi berbagai jenis ABK, yaitu diantaranya: anak dengan hambatan penglihatan (tunanetra), anak dengan hambatan penglihatan (tunarungu), anak dengan hambatan fisik (tunadaksa), anak dengan hambatan sosial emosi (tunalaras), anak dengan hambatan intelektual (tunagrahita), lamban belajar, autis, ADHD, anak dengan kesulitan belajar spesifik, anak cerdas istimewa bakat istimewa (CIBI) yang juga merupakan anak berkebutuhan khusus (Virinkoski et al, 2020).…”
Section: Hasil Dan Pembahasanunclassified